2015
DOI: 10.15288/jsad.2015.76.749
|View full text |Cite
|
Sign up to set email alerts
|

How Harmonious and Obsessive Passion for Alcohol and Marijuana Relate to Consumption and Negative Consequences

Abstract: ABSTRACT. Objective: Although the concepts of harmonious and obsessive passion have been productive in explaining why people eagerly engage in such activities as sports, Internet use, and gambling, previous research has not yet extended these models to explain alcohol and marijuana use among college students. The current research was conducted to clarify the relationships among harmonious and obsessive passion, alcohol and marijuana use, and negative consequences. Method: Two studies were conducted using onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 44 publications
(52 reference statements)
5
21
2
Order By: Relevance
“…This passion model offers an alternative to the abstinence-only or "all drugs are bad" approach that, instead of pathologizing the use of psychedelics, considers that their use may lead to positive emotions and psychological well-being. The passionate model has been applied to MDMA [ 54 ] and marijuana [ 55 , 56 ] suggesting that some patterns of regular use may indeed be experienced as positive and are not necessarily associated with negative outcomes. A focus on benefit maximization in harm reduction therapy appears even more acceptable in the case of classic psychedelics given their well-documented low potential for dependence or physical harm [ 57 ].…”
Section: Harm Reduction and Psychedelicsmentioning
confidence: 99%
“…This passion model offers an alternative to the abstinence-only or "all drugs are bad" approach that, instead of pathologizing the use of psychedelics, considers that their use may lead to positive emotions and psychological well-being. The passionate model has been applied to MDMA [ 54 ] and marijuana [ 55 , 56 ] suggesting that some patterns of regular use may indeed be experienced as positive and are not necessarily associated with negative outcomes. A focus on benefit maximization in harm reduction therapy appears even more acceptable in the case of classic psychedelics given their well-documented low potential for dependence or physical harm [ 57 ].…”
Section: Harm Reduction and Psychedelicsmentioning
confidence: 99%
“…Moreover, both passions were positively correlated to marijuana use. However, harmonious passion for marijuana was related to higher levels of marijuana use than obsessive passion, but there was no significant difference between obsessive and harmonious passion in terms of predicting marijuana problems (Steers et al, 2015). There is currently no other research on the effects of passion for religion in relation to substance use.…”
Section: Harmonious and Obsessive Passionmentioning
confidence: 90%
“…Two studies found both harmonious and obsessive passion to be positively associated with gambling, but harmonious passion was associated with more positive psychological outcomes (e.g., enjoyment, challenge, control) whereas obsessive passion was associated with negative outcomes (e.g., gambling larger sums, feelings of guilt, and perceptions of being judged by others; Mageau et al, 2005;Rousseau et al, 2002). Specifically in relation to substance use, higher levels of harmonious passion for alcohol predicted higher levels of alcohol consumption (Steers et al, 2015), but lower levels of alcohol problems. Conversely, greater obsessive passion was associated with higher levels of drinking and alcohol problems.…”
Section: Harmonious and Obsessive Passionmentioning
confidence: 96%
See 2 more Smart Citations